Reliability of semiquantitative assessment of osteophytes and subchondral cysts on tomosynthesis images by radiologists with different levels of expertise - Hayashi, Daichi; Xu, Li; Gusenburg, Jeffrey; Roemer, Frank; Hunter, David J.; Li, Ling; Guermazi, Ali (Diagnostic and Interventional Radiology, 2014)
We aimed to assess reliability of the evaluation of osteophytes and subchondral cysts on tomosynthesis images when read by radiologists with different levels of expertise.Forty subjects aged >40 years had both knees evaluated using tomosynthesis. Images were read by an "experienced" reader (musculoskeletal radiologist with prior experience) and an "inexperienced" reader (radiology resident with no prior experience). Readers graded osteophytes from 0 to 3 and noted the presence/absence of subchondral cysts in four locations of the tibiofemoral joint. Twenty knees were randomly selected and re-read. Inter- and intrareader reliabilities were calculated using overall exact percent agreement and weighted ? statistics. Diagnostic performance of the two readers was compared against magnetic resonance imaging readings by an expert reader (professor of musculoskeletal radiology).The experienced reader showed substantial intrareader reliability for graded reading of osteophytes (90%, ?=0.93), osteophyte detection (95%, ?=0.86) and cyst detection (95%, ?=0.83). The inexperienced reader showed perfect intrareader reliability for cyst detection (100%, ?=1.00) but intrareader reliability for graded reading (75%, ?=0.79) and detection (80%, ?=0.61) of osteophytes was lower than the experienced reader. Inter-reader reliability was 61% (?=0.72) for graded osteophyte reading, 91% (?=0.82) for osteophyte detection, and 88% (?=0.66) for cyst detection. Diagnostic performance of the experienced reader was higher than the inexperienced reader regarding osteophyte detection (sensitivity range 0.74-0.95 vs. 0.54-0.75 for all locations) but diagnostic performance was similar for subchondral cysts.Tomosynthesis offers excellent intrareader reliability regardless of the reader experience, but experience is important for detection of osteophytes.
EVALuna2:14440